Indikator Atribut Sensori Kopi Specialty Asal Jawa Barat Berbasis Komponen Biokimia - Anandya Vanessa Isnidayu; Anggoro Cahyo Sukartiko; Makhmudun Ainuri (Jurnal Tanaman Industri dan Penyegar, 2020)
Assessing coffee sensory quality is generally carried out by panelists using cup testing with reference to the Specialty Coffee Association of America (SCAA) standards. A high level of sensitivity sensory is essential thus it must be done by trained panelists. Given the limitations of the method, a deeper study is required to obtain a standard of assessment of coffee sensory quality based on more reliable and precise analytical methods, one of which is biochemical components. This study was aimed to analyze the sensory quality and biochemical components of Arabica coffee and determine the indicators of sensory attributes based on those biochemical components. The study was conducted at two Arabica coffee-producing areas in West Java from May to September 2019. The biochemical components analyzed included caffeine, trigonelline, chlorogenic acid (CGA), sucrose, and lipid, while the sensory attributes assessed were aroma, flavor, aftertaste, acidity, body, balance, uniformity, sweetness, clean cup, and overall. The survey method with stratified and simple random sampling was used and followed by Two-way Anova and Partial Least Square analysis. Results showed variations in the biochemical content of coffee from the two areas. Lipid has a positive correlation with the aroma and flavor attributes, and negatively correlated with the body attribute. Caffeine has a negative correlation with the aftertaste attribute, whereas CGA has a negative correlation with the acidity attribute. Correlation between biochemical components with sensory attributes showed that the biochemical content acts as an indicator of sensory attributes.